2009
DOI: 10.1186/1476-7120-7-23
|View full text |Cite
|
Sign up to set email alerts
|

Doppler ultrasonography and exercise testing in diagnosing a popliteal artery adventitial cyst

Abstract: We describe popliteal arterial adventitial cystic disease which causes intermittent claudication in a young athletic man, with atypical manifestation, without loss of foot pulses on knee flexion nor murmur in the popliteal fossa. The findings obtained from Magnetic Resonance Imaging were nondiagnostic. The diagnosis resulted from Echo-Doppler ultrasonography along with peak exercise testing. Ultrasonography also provided useful physiopathological informations suggesting that a popliteal artery adventitial cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 8 publications
0
22
0
5
Order By: Relevance
“…Similarly, a simple doppler image would not show changes in the blood flow in these cases. In some instances, the stenosis is visible only in images obtained during knee hyperflexion 27 , such as in case of the Ishikawa sign in physical examination. However, this manoeuvre can also fail as Taurino et al 27 reported a case of the popliteal artery affected with CAD with no luminal stenosis on MRA and no peripheral perfusion deficit on duplex ultrasound seen during knee hyperflexion.…”
Section: Diagnostics Of Cadmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, a simple doppler image would not show changes in the blood flow in these cases. In some instances, the stenosis is visible only in images obtained during knee hyperflexion 27 , such as in case of the Ishikawa sign in physical examination. However, this manoeuvre can also fail as Taurino et al 27 reported a case of the popliteal artery affected with CAD with no luminal stenosis on MRA and no peripheral perfusion deficit on duplex ultrasound seen during knee hyperflexion.…”
Section: Diagnostics Of Cadmentioning
confidence: 99%
“…In some instances, the stenosis is visible only in images obtained during knee hyperflexion 27 , such as in case of the Ishikawa sign in physical examination. However, this manoeuvre can also fail as Taurino et al 27 reported a case of the popliteal artery affected with CAD with no luminal stenosis on MRA and no peripheral perfusion deficit on duplex ultrasound seen during knee hyperflexion. In addition, MRA failed to visualise the adventitial cyst clearly in this case, and the definite diagnosis of popliteal artery CAD came from duplex ultrasound.…”
Section: Diagnostics Of Cadmentioning
confidence: 99%
See 2 more Smart Citations
“…DUS provides useful information in suggesting CAAD less invasively subsequent MDCT with 3-dimensional volume rendering and MRA excludes a systemic atherosclerotic lesion. 8) Open surgery included removal of cystic lesion with CFA and subsequent interposition using great saphenous vein graft is the best therapeutic option for CAAD. Percutaneous cystic aspiration under US guide is not always possible because of the high viscosity of the content and multillocular cyst and a high recurrence rate has been described due to the mucin-secreting cells which still remain.…”
Section: Cystic Adventitial Disease Of the Common Femoral Arterymentioning
confidence: 99%